Strategi Pemasaran Syariah Batik Jambi: Studi Kasus Toko Batik Jambi Ardiah - Ranti Arianti; Maulana Yusuf; Taufik Ridho (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Sharia marketing strategy is a plan or planning of entrepreneurs and companies which is the implementation of the concept of determining prices, targets, and procedures for promotion and expansion of ideas, goods and services for exchange that meets customer needs. This study aims to find out the buying interest and consumer interest in Jambi batik. This research is a qualitative research, because this research instrument uses interviews to get data, The population in this study is consumers who buy Jambi batik products or batik at Ardiah stores. A sample of 73 people was determined, with interview techniques. The results of the study found that: Sharia marketing strategy significantly had a positive effect on buying interest with a value above 0.477 meaning that 47.7/% of Jambi batik marketing could explain its influence on Jambi batik buying interest, while 52.3% was explained by other factors.